Hubungan Usia Menarche Dengan Kejadian Dismenorea Pada Remaja - Arlyana Hikmanti; Nur Adriani, Fauziah Hanum; Yanti, Linda (Indonesian Journal Publisher, 2025)
Background: The prevalence of dysmenorrhea in adolescents is reported to be very high in various countries, causing disruption to adolescent activities. Objective: This study aims to determine the prevalence of dysmenorrhea in adolescents and examine the relationship between age at menarche and current age of adolescents with the incidence of dysmenorrhea as an effort to support effective reproductive health strategies among adolescent girls. Methods: This study used a quantitative descriptive study with a survey approach to describe the age at menarche and the incidence of dysmenorrhea in adolescents. This study was conducted in high schools in the Purwokerto area, from January to March 2025. The population was all 21,245 adolescent girls in the Purwokerto area. Data collection used primary data, namely respondents completing a questionnaire regarding current age, age at menarche, and the incidence of dysmenorrhea. Results: The majority of respondents were aged 14-16 years (54.4%), experienced early menarche (93.5%), and 72.3% experienced dysmenorrhea. There was no relationship between age at menarche and the incidence of dysmenorrhea. Conclusion: Most respondents aged 14-16 years, with a high school education level, experienced early menarche and dysmenorrhea, and there was no significant relationship between age of menarche and the incidence of dysmenorrhea.